Pokolenie Zet jako „wymagający gracz” współczesnego rynku pracy - Wawrzonek , Anna (Studia Edukacyjne, 2023)
The aim of this article is to present reflections on the Zet generation/Gen Z, with particular emphasis on the context of the labor market. The analysis of available reports and studies will make it possible to point out the strengths, opportunities, and expectations verbalized by the representatives of Gen Z themselves and the expectations placed upon them. The picture of the Gen Z presented below may become the starting point for determining or modifying educational and advisory solutions aimed at supporting young people in building lifelong careers.